Assessment of Hereditary Retinal Degeneration in the English Springer Spaniel Dog and Disease Relationship to an RPGRIP1 Mutation - Kristina Narfström; Manbok Jeong; Jennifer Hyman; Richard W. Madsen; Tomas F. Bergström (Hindawi Limited, 2012)
Intensive breeding and selection on desired traits have produced high rates of inherited diseases in dogs. Hereditary retinal degeneration, often called progressive retinal atrophy (PRA), is prevalent in dogs with disease entities comparable to human retinitis pigmentosa (RP) and Leber's congenital amaurosis (LCA). Recent molecular studies in the English Springer Spaniel (ESS) dog have shown that PRA cases are often homozygous for a mutation in the RPGRIP1 gene, the defect also causing human RP, LCA, and cone rod dystrophies. The present study characterizes the disease in a group of affected ESS in USA, using clinical, functional, and morphological studies. An objective evaluation of retinal function using electroretinography (ERG) is further performed in a masked fashion in a group of American ESS dogs, with the examiner masked to the genetic status of the dogs. Only 4 of 6 homozygous animals showed clinical signs of disease, emphasizing the need and importance for more precise studies on the clinical expression of molecular defects before utilizing animal models for translational research, such as when using stem cells for therapeutic intervention.